2007
DOI: 10.1038/sj.jid.5700921
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for the Phospholipase D2-Aquaporin-3 Signaling Module in Early Keratinocyte Differentiation: Production of a Phosphatidylglycerol Signaling Lipid

Abstract: In keratinocytes aquaporin-3 (AQP3), an efficient glycerol transporter, is associated with phospholipase D2 (PLD2) in caveolin-rich membrane microdomains. PLD catalyzes both phospholipid hydrolysis to produce phosphatidate and a transphosphatidylation reaction using primary alcohols to generate phosphatidylalcohols. As PLD2 can utilize the physiological alcohol glycerol to form phosphatidylglycerol (PG), we hypothesized that AQP3 provides glycerol to PLD2 for PG synthesis, which then modulates keratinocyte fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 37 publications
5
100
2
Order By: Relevance
“…However, the polyunsaturated isoforms of PG appear to promote differentiation at the expense of proliferation [75,76]. This evidence supports the conclusion that DNA synthesis is inhibited by the PG produced by PLD2 [76].…”
Section: Mammalian Cellssupporting
confidence: 77%
See 1 more Smart Citation
“…However, the polyunsaturated isoforms of PG appear to promote differentiation at the expense of proliferation [75,76]. This evidence supports the conclusion that DNA synthesis is inhibited by the PG produced by PLD2 [76].…”
Section: Mammalian Cellssupporting
confidence: 77%
“…PG from Hen's eggs [76] (44 % 18:0/16:0) accelerates proliferation, but this is inhibited by PG from Glycine max [75] (72 % 18:2/18:3). However, the polyunsaturated isoforms of PG appear to promote differentiation at the expense of proliferation [75,76]. This evidence supports the conclusion that DNA synthesis is inhibited by the PG produced by PLD2 [76].…”
Section: Mammalian Cellsmentioning
confidence: 99%
“…It is clear that AQP3 plays a role in keratinocyte proliferation in both human and mouse epidermis (Hara-Chikuma and Verkman, 2008b;Nakahigashi et al, 2011) and AQP3-facilitated water transport is important for keratinocyte migration in the mouse (Hara-Chikuma and Verkman, 2008a). Furthermore, despite some debate over a role for AQP3 in keratinocyte differentiation in mice (Bollag et al, 2007;Hara-Chikuma et al, 2009;Kim and Lee, 2010), evidence in human keratinocytes supports a role for AQP3 in the negative regulation of differentiation (and promotion of proliferation) through the downregulation of Notch1, a known mediator of keratinocyte differentiation (Guo et al, 2013).…”
Section: Aqp3mentioning
confidence: 99%
“…13,14 ). In a recent study, we have shown that manipulations that alter the function of this PLD2/AQP3/PG signaling module can inhibit epidermal keratinocyte proliferation and promote differentiation ( 17 ).…”
Section: Methodsmentioning
confidence: 99%